Трансцендентноста и иманентноста на Бога во патристичката философија - Ѓорѓевиќ, Милан (Православен богословски факултет „Свети Климент Охридски“ – Скопје, 2023)
The term “theology” can be reduced to two meanings established since the epoch of the Byzantine Middle Ages, of which the first and basic meaning refers to the experience of knowing God and the immediate communion with Him. The second meaning, on the other hand, covers the conceptualization and expression of that experience with the language of various discourses – starting from philosophy, through rhetoric, and all the way to art and music. These two meanings are mutually related and mutually conditioned. However, in this paper we will not delve into the question of the their historical emergence and development, as well as their connection and mutual relationship. Instead, we will focus on one question that acts as a basic assumption of theology in both its senses, namely, the belief that God can be known and that experience can be discursively expressed. With this aim, we will dwell on the question of the transcendence and immanence of God and the ways in which that question is answered within the Byzantine theological-philosophical tradition. For this purpose, we will analyze three basic discourses, through which Christianity responds to it: the biblical, the liturgical-homilitic and the philosophical discourse.